N-truncated Aβ4–x peptides in sporadic Alzheimer’s disease cases and transgenic Alzheimer mouse models - Oliver Wirths; Susanne Walter; Inga Kraus; Hans W. Klafki; Martina Stazi; Timo J. Oberstein; Jorge Ghiso; Jens Wiltfang; Thomas A. Bayer; Sascha Weggen (Alzheimer’s Research & Therapy, 2017)
Abstract Background The deposition of neurotoxic amyloid-β (Aβ) peptides in plaques in the brain parenchyma and in cerebral blood vessels is considered to be a key event in Alzheimer’s disease (AD) pathogenesis. Although the presence and impact of full-length Aβ peptides such as Aβ1–40 and Aβ1–42 have been analyzed extensively, the deposition of N-terminally truncated Aβ peptide species has received much less attention, largely because of the lack of specific antibodies. Methods This paper describes the generation and characterization of novel antibodies selective for Aβ4–x peptides and provides immunohistochemical evidence of Aβ4–x in the human brain and its distribution in the APP/PS1KI and 5XFAD transgenic mouse models. Results The Aβ4–x staining pattern was restricted mainly to amyloid plaque cores and cerebral amyloid angiopathy in AD and Down syndrome cases and in both AD mouse models. In contrast, diffuse amyloid deposits were largely negative for Aβ4–x immunoreactivity. No overt intraneuronal staining was observed. Conclusions The findings of this study are consistent with previous reports demonstrating a high aggregation propensity of Aβ4–x peptides and suggest an important role of these N-truncated Aβ species in the process of amyloidogenesis and plaque core formation.